Surface distribution of small-scale magnetic field on the active cool star LQ Hydrae - Kochukhov O.; Hackman T.; Lehtinen J. J. (EDP SCIENCES, 2025)
It is well known that small-scale magnetism dominates the surface magnetic field topologies of active late-type stars. However, little information is available on the spatial distribution of this key magnetic field component. Here, we take advantage of the recently developed magnetic field diagnostic procedure relying on the magnetic intensification of iron atomic lines in the optical. We extend this methodology from measuring a single average field strength value to simultaneous Doppler imaging reconstruction of the two-dimensional maps of temperature and magnetic field strength. We applied this novel surface mapping approach to two spectroscopic data sets of the young active Sun-like star LQ Hya. For both epochs, we found a fairly uniform field strength distribution, apart from a latitudinal trend of the field strength increasing from 1.5–2.0 kG at low latitudes to 3.0–3.5 kG, close to the rotational poles. This distribution of the small-scale field does not display a clear correlation with the locations of temperature spots or the global magnetic field structure reconstructed for the same epochs.